2020
DOI: 10.1016/j.jcrysgro.2019.125436
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the growth interface shape on the defect characteristics in the facet region of 4H-SiC single crystals

Abstract: Two 75mm 4H-SiC single crystals are grown by the physical vapor transport (PVT) technique, using different insulation materials. The insulation material of higher thermal conductivity led to an increased radial temperature gradient. The evolution of the growth front was monitored using the in-situ computed tomography (CT). A slightly bent growth interface and a bigger facet are formed during the growth applying a lower radial temperature gradient while a smaller facet and steeper crystal flanks are formed in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…[8] Several scholars have reported that crystal growth along a tilt from [0001] toward [1 210] is suitable for stabilizing polytype. [9,10] However, to the best of our knowledge, there is no study on the dislocation analysis of crystals along a tilt from [0001] toward [1 210] and [1 100] in conjunction with stress analysis. In this paper, we studied dislocation density using the Alexander-Haasen model with 3D and time-dependent calculations reported elsewhere, [11,12] including crystal growth and cooling processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Several scholars have reported that crystal growth along a tilt from [0001] toward [1 210] is suitable for stabilizing polytype. [9,10] However, to the best of our knowledge, there is no study on the dislocation analysis of crystals along a tilt from [0001] toward [1 210] and [1 100] in conjunction with stress analysis. In this paper, we studied dislocation density using the Alexander-Haasen model with 3D and time-dependent calculations reported elsewhere, [11,12] including crystal growth and cooling processes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] Several scholars have reported that crystal growth along a tilt from [0001] toward false[12¯10false]$[ {1\bar 210} ]$ is suitable for stabilizing polytype. [ 9,10 ] However, to the best of our knowledge, there is no study on the dislocation analysis of crystals along a tilt from [0001] toward false[12¯10false]$[ {1\bar 210} ]$ and false[11¯00false]$[ {1\bar 100} ]$ in conjunction with stress analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For more specific inquiries of the growth process, advanced 3D imaging can be employed. Such sophisticated systems are not commercially viable due to the technical complexities; however, in an R&D environment, they have been proven to be incredibly valuable in considering problems such as the evolution of the crystal’s facet during growth [ 184 ], the specific morphology of the powder source for the determination of dynamic source material properties [ 185 ], as well as the impact of the curvature of the growth interface on the defect distribution in the resulting crystal [ 186 ].…”
Section: Silicon Carbide Materialsmentioning
confidence: 99%
“…The step structure on the as-grown surface of SiC crystals has been studied by several research groups [6][7][8][9][10][11][12]. On the (0001) facet of 4H-SiC crystals grown in the c-axis direction, surface steps of half-unit cell height (0.5 nm) were predominantly observed, and they were often bunched into macrosteps of heights of approximately 6-10 nm.…”
Section: Introductionmentioning
confidence: 99%